Die gewerblichen Fortbildungsschulen in den Provinzen Posen und Westpreußen. Instrumente der Polenpolitik, Vorreiter des Staatsschulsystems und Elemente regionaler Entwicklungspolitik [The commercial training schools in the provinces of Posen and West Prussia. Instruments of Polish policy, pioneers of the state school system and elements of regional development policy] - Müller, Uwe (Studia Historiae Oeconomicae, 2009)
Stefan Kowal has repeatedly pointed out the lower level of education of the Polish population in the eastern provinces of Prussia compared to Germans and Jews. This deficit resulted from the clear differences in the social structures of the individual ethnic groups, which Stefan Kowal had also highlighted, and was exacerbated by the discrimination against the Polish language in the Prussian educational system. Even organic work, such as the awarding of scholarships by the Marcinkowski Association, could not fundamentally change this situation.1 The financially weak communities of the province of Posen had the worst elementary school conditions in the Prussian state, which was reflected in long school journeys, dilapidated school buildings, poorly trained teachers and, above all, severely overcrowded classes. The state repeatedly took police and legal action against striking students and their parents who were simply demanding the reintroduction of religious instruction in the mother tongue.